The role of podcast as an innovative learning tool in health sciences education: Perceptions and impact - Martinez-Guzman, Marco Alonso; Lopez-Vazquez, Alexandra Zairabel; Gonzalez-Ramos, Isaura Araceli; Toral-Murillo, María Valentina (Journal of Education and e-Learning Research, 2025)
A podcast is a downloadable audio file with a significant impact on teaching due to its availability and repetitive on-demand playback. Educational podcasts are created through a didactic planning process to provide students with cognitive advantages, enhancing their analysis, selection skills, and content dissemination. The purpose was to determine the effectiveness of using podcasts compared to other teaching strategies for learning in health sciences students. The study was an analytical cross-sectional design conducted with a sample of 52 health sciences students, who were asked to develop a designated podcast, followed by answering a survey about their perception of using podcasts, as well as identifying strengths and weaknesses. Our findings indicated that most participants enjoyed using podcasts, highlighting their innovative characteristics and the opportunity they provide to spread information; they also reported increased learning. The advantages included the lack of need to record their faces, the ability to make several recording attempts, and the generation of their own knowledge. Disadvantages included the need for editing, the presence of visual or kinesthetic learning preferences, and stuttering while speaking. Therefore, practical implications suggest that podcasts stand out as an innovative educational tool among health sciences students, with clear perceived strengths and few weaknesses.